ACCURACY OF A LOW-COST NOVEL COMPUTER-VISION DYNAMIC MOVEMENT ASSESSMENT: POTENTIAL LIMITATIONS AND FUTURE DIRECTIONS - Wetterling, Friedrich (My University, 2016)
The aim of the study was to perform a preliminary validation of a low cost markerless motion capture system (CAPTURE) against an industry gold standard (Vicon). Measurements of knee valgus and flexion during the performance of a countermovement jump (CMJ) between CAPTURE and Vicon were compared. After correction algorithms were applied to the raw CAPTURE data acceptable levels of accuracy and precision were achieved. The knee flexion angle measured for three trials using Capture deviated by −3.8° ± 3° (left) and 1.7° ± 2.8° (right) compared to Vicon. The findings suggest that low-cost markerless motion capture has potential to provide an objective method for assessing lower limb jump and landing mechanics in an applied sports setting. Furthermore, the outcome of the study warrants the need for future research to examine more fully the potential implications of the use of low-cost markerless motion capture in the evaluation of dynamic movement for injury prevention.
PUBLISHED
Keywords: Low Cost, Markerless, Motion Capture, Movement Assessment, ACL